Synthesis and characterization of a ring-opening oxaspiro comonomer by a novel catalytic method for denture base resins - Ranganathan Ajay; Vikraman Rakshagan; Rajamani Ganeshkumar; Elumalai Ambedkar; Shafiullah RahmathShameem; Kanagesan Praveena (Wolters Kluwer Medknow Publications, 2021)
Background: 3,9-Dimethylene-1,5,7,11-tetraoxaspiro[5,5]undecane (DMTOSU) is a double ring-opening monomer that exhibits expansion upon polymerization and may be used as a denture base resin's comonomer to offset or minimize polymerization shrinkage. It's synthesis by transesterification reaction (TE) catalyzed by distannoxane is not reported in the literature. The synthesis became the prime concern because this monomer is hardly available commercially. Purpose: The purpose is to confirm the DMTOSU synthesis and compare the synthesized monomers obtained by two different catalytic processes through Fourier transform infrared (FTIR) and nuclear magnetic resonance (NMR) spectroscopies. Materials and Methods: Scheme I synthesis was by TE catalyzed by dichlorotetrabutyl distannoxane (DCBS) yielding M1 monomer. Scheme II synthesis was catalyzed by dibutyltin oxide-carbon disulfide (DBTO-CS2) yielding M2 monomer. Results: The appearance of a characteristic peak at 1212 cm−1 in FTIR spectrum, a doublet at δ 4.95 in 1H-NMR spectrum and a peak at δ 117.12 in 13C-NMR spectrum confirmed the synthesis of DMTOSU-M1catalyzed by DCBS, which is not significantly different from DMTOSU-M2 catalyzed by DBTO-CS2. Conclusion: The catalytic action of DCBS is a successful alternative to the DBTO-CS2 catalysis in DMTOSU synthesis.